The Influence of the Maqashid Syariah Index Based on the Thought of Asy-Syatibi on the Market Share of Islamic Commercial Banks in Indonesia - fatih zaidan; Shaifurrokhman Mahfudz (Universitas Islam Negeri Sumatera Utara, 2026)
This study examines whether the implementation of Maqashid al-Shariah—grounded in al-Shatibi’s higher objectives framework and operationalized through the Maqashid Shariah Index (MSI)—contributes to increasing the market share of Islamic commercial banks (Bank Umum Syariah) in Indonesia. Using an explanatory quantitative approach, the research employs secondary data from annual reports and OJK Islamic banking statistics for the 2016–2023 period. The MSI is measured through three dimensions: tahdzib al-fard (human development), iqamah al-‘adl (justice), and jalb al-maslahah (public welfare), with total assets, capital adequacy ratio (CAR), and number of branches considered as control variables. Panel data estimation indicates that the fixed effects model is the most appropriate specification. The results show that, partially, only tahdzib al-fard is statistically significant, yet its negative coefficient should be interpreted cautiously due to extremely low variation in the data. Meanwhile, iqamah al-‘adl and jalb al-maslahah are not statistically significant on an individual basis. Simultaneously, the MSI dimensions jointly affect market share, although bank-specific characteristics remain more dominant in explaining market share differences across banks. These findings imply that maqashid-based performance may function more as a long-term, reputational and legitimacy mechanism rather than an immediate driver of market share expansion.